Eco-sustainable valorization of Cystoseira abiesmarina and Caulerpa prolifera - Rosa, Gonçalo Pereira da (2024)
The cosmeceutical industry has recognized the significant bioactive potential of marine macroalgae and has increasingly focused attention on these organisms. A growing number of products now include extracts derived from various macroalgae species or even isolated compounds sourced from them. Nevertheless, many species remain largely uninvestigated, indicating a gap worth exploring. This PhD thesis aims to address this gap by investigating the cosmeceutical potential of two understudied marine macroalgae species from the phytochemical and bioactivity aspects, Gongolaria abies-marina and Caulerpa prolifera. The study focuses on exploring their phytochemical composition, optimizing environmentally friendly extraction methods, assessing their cosmeceutical potential, and on the structural modification of the compounds identified to enhance their bioactive properties. For the study of Gongolaria abies-marina, a novel approach to optimize extraction parameters for ultrasound- and microwave-assisted extraction methods was introduced, aiming to enhance the anti-aging activities of extracts from this macroalga. Through systematic variation of the parameters and statistical analysis, optimal conditions for maximizing cosmeceutical potential were identified. For ultrasound-assisted extraction (UAE), the best results were achieved using ethyl acetate as the solvent, a 1:4 solid/liquid ratio, and a 15- minute extraction time, leading to high yield and effective inhibition of tyrosinase and elastase. For microwave-assisted extraction (MAE), optimal conditions were ethanol as the solvent, a 1:4 solid/liquid ratio, and a 10-minute extraction time, resulting in superior antioxidant activity and significant tyrosinase inhibition. Chemical characterization revealed that both methods produced less complex and more selective extracts when compared to conventional methods. MAE showed higher selectivity, extracting mainly polyphenolic compounds, while UAE extracted a broader range of compounds, including diterpenoids and sterols, some identified for the first time in Gongolaria abies-marina. The identification of compounds with high anti-aging potential opens new opportunities for their use in anti-aging formulations. The phytochemical study of Caulerpa prolifera revealed its potential for cosmeceutical applications, identifying it as a promising source of extracts and compounds with interesting enzyme inhibitory activities, especially against tyrosinase, despite limited overall antioxidant capacity. The phytochemical study of Caulerpa prolifera revealed its potential for cosmeceutical applications, identifying it as a promising source of extracts and compounds with interesting enzyme inhibitory activities, especially against tyrosinase, despite limited overall antioxidant capacity.The phytochemical study of Caulerpa prolifera revealed its potential for cosmeceutical applications, identifying it as a promising source of extracts and compounds with interesting enzyme inhibitory activities, especially against tyrosinase, despite limited overall antioxidant capacity. This work presents the most complete assessment of the lipophilic profile of this species to date, a profile composed mainly of saturated and unsaturated fatty acids and di-(2- ethylhexyl) phthalate, an endocrine disruptor, which might be either biosynthesized or bioaccumulated by the algae. Fractionation of the extract led to subfractions with varying bioactivities due to changes in chemical composition. Enhanced inhibitory activity against elastase and collagenase was observed in certain subfractions, associated with the increase in proportion of 1-octadecanol. Antioxidant activity decreased with the loss of specific compounds like β-sitosterol, erucic acid, nervonic acid, and lignoceric acid. The phytochemical analysis contributed to understanding the potential effects of the various compounds present in Caulerpa prolifera on its bioactivities, leading to a more comprehensive valorization of this macroalga as a promising source of cosmeceutical ingredients. This work also aimed to perform structural modifications on select molecules sourced from the phytochemical investigation into Gongolaria abies-marina and Caulerpa prolifera. Stigmasterol, β-sitosterol, and phytol were selected from the pool of identified compounds for subsequent modifications. Ten derivatives of each starting compound were obtained, with good to moderate yields, by esterification reactions with benzoic, cinnamic, furoic, and thiophene- 2-carbonic acids. The best results were obtained for tyrosinase and hyaluronidase inhibition. Phytyl 4-methoxybenzoate (3d) was the most active compound against tyrosinase (IC₅₀ = 27.94 μM), with this modification providing a 2.8-fold increase compared to phytol (3) (IC₅₀ = 74.47 μM). Other methoxy group substitutions on benzoate nucleus highly reduced the activity. For hyaluronidase, β-sitosterol (2) showed strong activity (12.97 μM), and the derivatives sitoster-3-yl benzoate (2a) (3.45 μM) and sitoster-3-yl 2- methoxybenzoate (2b) (2.88 μM) exhibited 3.8- and 4.5-times higher potency, respectively, indicating that benzoyl and 2-methoxybenzoyl groups enhance enzyme interaction. Moving the methoxyl group to positions 3 (2c) or 4 (2d) greatly influenced potency (12.63 and 71.77 μM, respectively). Other derivatives showed no activity, highlighting the importance of specific structural modifications for inhibitory efficacy. This study is the first to report the anti-aging potential of these derivatives. In conclusion, this work significantly contributed to the valorization of Gongolaria abies-marina and Caulerpa prolifera by increasing the knowledge about their phytochemical profiles and describing for the first time the anti-aging potential of their extracts, their respective constituents and the semi-synthetic derivatives.